Adverse Reactions in Allogeneic Blood Donors: A Tertiary Care Experience from a Developing Country - Sadia Sultan; Mohammad Amjad Baig; Syed Mohammed Irfan; Syed Ijlal Ahmed; Syeda Faiza Hasan (Oman Medical Journal, 2016)
Objectives: Fragmented blood transfusion services along with an unmotivated blood donation culture often leads to blood shortage. Donor retention is crucial to meet the increasing blood demand, and adverse donor reactions have a negative impact on donor return. The aim of this study was to estimate adverse donor reactions and identify any demographic association.